Treating rural water without introducing harmful substances - OGEDENGBE, O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The coliform count on the stream water studied was high. The water is a direct source of drinking water to some rural communities. A previous study established that about 100 ppm of chlorine in the form of chlorox was sufficient to bring the coliform Most Portable Number (MPN) from about 11,000 per 100ml down to within allowable standard of one per 100ml of water sample. There is some concern that turbid water contain organic matter which when chlorinated could give rise to formation of chloroform and possibly other chlorine-based compound of the of the trihalmethane family which conceivably could be carcinogenic. This prompt design and contruction of a simple system of turbidity removal and chlorination. With this system, the required chlorine dosage even went down to about 50 ppm.